Impact of economic development upon the environment. - Alleyne, Frank W. (1992)
Uses the 'materials balance' model to demonstrate the structural relationships between production and the environment. Examines the consequences of abuse of the environment and the implications for economic and social progress. Reviews some options for controlling pollution and management of the environment.